Self-Assembly of Pulverized Nanoparticles: An Approach to Realize Large-Capacity, Long-Lasting, and Ultra-Fast-Chargeable Na-Ion Batteries - Park, Jun-Hyoung; Choi, Yong-Seok; Kim, ChangHyeon; Byeon, Young-Woon; Kim, Yongmin; Lee, Byeong-Joo; Ahn, Jae-Pyoung; Ahn, Hyojun; Lee, Jae-Chul (AMER CHEMICAL SOC, 2021)
The fabrication of battery anodes simultaneously exhibiting large capacity, fast charging capability, and high cyclic stability is challenging because these properties are mutually contrasting in nature. Here, we report a rational strategy to design anodes outperforming the current anodes by simultaneous provision of the above characteristics without utilizing nanomaterials and surface modifications. This is achieved by promoting spontaneous structural evolution of coarse Sn particles to 3D-networked nanostructures during battery cycling in an appropriate electrolyte. The anode steadily exhibits large capacity (similar to 480 mAhg(-1)) and energy retention capability (99.9%) during >1500 cycles even at an ultrafast charging rate of 12 690 mAg(-1) (15C). The structural and chemical origins of the measured properties are explained using multiscale simulations combining molecular dynamics and density functional theory calculations. The developed method is simple, scalable, and expandable to other systems and provides an alternative robust route to obtain nanostructured anode materials in large quantities.